Aboveground herbivory causes belowground changes in twelve oak Quercus species: a phylogenetic analysis of root biomass and non‐structural carbohydrate storage. Issue 10 (23rd August 2021) - Perkovich, Cynthia; Ward, David
Abstract : Plant ecosystem structure is understood to be a result of complex multitrophic interactions. Most multitrophic studies focus on plant aboveground adaptations to aboveground herbivore pressures, neglecting belowground adaptations in response to aboveground damage. Differential investment in root structures may allow plants to compensate for tissue loss or damage due to herbivores. Furthermore, phylogeny may constrain a plant's ability to adapt belowground. We examined the belowground responses of 12 species of oak Quercus to varying locations and intensities of simulated herbivore damage. We first established that oak belowground traits responded to aboveground herbivory by measuring patterns of investment in coarse versus fine root structures and re‐allocation of non‐structural carbohydrates (NSC) to root storage. We then tested whether phylogeny could explain variations in investment patterns using phylogenetic independent contrasts. Plant adaptations to aboveground herbivory included allocating biomass and carbon reserves to root structures, depending on the location and intensity of herbivore damage. NSC re‐allocation to root storage was observed when oak species experienced any type of damage, but damage to lateral tissues caused a greater re‐allocation than apical damage or control treatments. We found that most belowground responses to aboveground herbivory are species‐specific and may be adapted for environmental conditions or type of herbivory. Some responses to herbivore damage, such as changes in fine‐root mass and root sugar concentrations, were phylogenetically constrained. Phylogenetic constraints generally occur when there is severe damage at the apical meristem. Plants may adapt to aboveground tissue loss due to varying herbivore pressures (i.e. varying location and intensity of damage) by differentially investing in root types and NSC re‐allocation to root storage. Understanding linkages between and phylogenetic constraints of plant belowground responses to aboveground herbivory will improve our understanding of the ecological processes involved in multitrophic interactions.